2016
DOI: 10.5867/medwave.2016.11.6809
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, beliefs and attitudes report on patient care and safety in undergraduate students: validating the modified APSQ-III questionnaire

Abstract: This study shows that the APSQ-III modified survey is valid and could be used in Argentina and the region to measure the impact of incorporating patient safety topics in the medical curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Similarly, in a report investigating maternal mortality in the Gaza-Strip, clinicians reported that they felt unsupported by management in case of adverse events 48. However, similar discrepancies between the acknowledgement that errors are inevitable, but that professionals should not make mistakes were also found internationally,28 31 33 35 49 50 possibly reflecting the ideal for professionals not to make mistakes. The understanding of this discrepancy, between error inevitability and the ideal of professionals avoiding them, needs to be focused on in further training as well as by developing more effective systems to deal with errors openly and learn from them 51 52…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, in a report investigating maternal mortality in the Gaza-Strip, clinicians reported that they felt unsupported by management in case of adverse events 48. However, similar discrepancies between the acknowledgement that errors are inevitable, but that professionals should not make mistakes were also found internationally,28 31 33 35 49 50 possibly reflecting the ideal for professionals not to make mistakes. The understanding of this discrepancy, between error inevitability and the ideal of professionals avoiding them, needs to be focused on in further training as well as by developing more effective systems to deal with errors openly and learn from them 51 52…”
Section: Discussionmentioning
confidence: 95%
“…Potential comparisons with other studies having used the APSQ framework are unsuitable, since some other authors used the APSQ-IV instead of the APSQ-III assessment tool [ 17 ], calculated their results from the raw scores of the different items and/or dimensions [ 14 ] instead of transforming scores into average positive response rates based on Nordén–Häag criteria, or adopted the aforementioned criteria but did not consider items with reverse scores, so that responses were all systematically grouped into agree (4 or 5) and disagree (1 or 2) to obtain the overall percentages [ 20 ], a fact that hinders any possible comparison through homogeneous scoring methods.…”
Section: Discussionmentioning
confidence: 99%
“…Several instruments to assess the knowledge and attitudes towards patient safety currently exist [ 10 , 11 ]. In this framework, the “Attitudes to Patient Safety Questionnaire” (APSQ-III, hereinafter) is a widely used instrument with outstanding psychometric properties [ 12 ] and has been validated in Spanish in a version with 7 response options [ 13 ] and with 5 response options [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations and other shorthand notations on prescriptions and orders increase the risk of medication errors. World Health Organization has published the curriculum for medical students working in health care institution dealing with patient care [3][4] .…”
Section: Introductionmentioning
confidence: 99%